2005
DOI: 10.1021/ja053003q
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Functionalized, Water-Dispersed Carbon Nanotubes at High Concentration

Abstract: Microwave-assisted functionalization of single-wall carbon nanotubes (SWNTs) in a mixture of nitric and sulfuric acids was carried out to synthesize highly water-dispersible nanotubes. Stable concentrations as high as 10 mg/mL were obtained in deionized water that are nearly 2 orders of magnitude higher than those previously reported. This was after only 3 min of functionalization reaction. Fourier transform infrared spectra showed the presence of carboxylated (-COOH) and acid sulfonated (-SO(2).OH or -SO(3)(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
226
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(246 citation statements)
references
References 26 publications
11
226
2
1
Order By: Relevance
“…Hence, it is indispensable to dissociate the bundles to make use of the outstanding properties of SWCNT. Non-covalent methods using surfactants [7,8] and polymers [9,10], and covalent chemical functionalization [11] have been widely used to disrupt the bundle structures in aqueous media. One of the major drawbacks of using surfactants and polymers is foam formation, which is not environmentally friendly, causing serious hurdles in industrial application [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is indispensable to dissociate the bundles to make use of the outstanding properties of SWCNT. Non-covalent methods using surfactants [7,8] and polymers [9,10], and covalent chemical functionalization [11] have been widely used to disrupt the bundle structures in aqueous media. One of the major drawbacks of using surfactants and polymers is foam formation, which is not environmentally friendly, causing serious hurdles in industrial application [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The average weight loss for the various derivates (1-SbF 6 , 1-Cl, 1-tartrate) was less than 10%, even at 500 o C, indicating high thermal stability (see supplementary material). This result stands in stark contrast to the case of MWCNTs modified via oxidative cutting method, where intensive decomposition of the MWCNTs begins at < 300 o C. 5 The TEM images showing the shapes of the nanotubes provided further support for the minimal change in their overall structure after modification. Moreover, the images clearly show that the soluble derivatives, 1-Cl and 1-tartrate, are individually dispersed, while the original MWCNTs are severely aggregated together.…”
Section: Resultsmentioning
confidence: 81%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17] Of the various techniques employed to dissolve CNTs in a suitable solvent, the oxidative cutting of CNTs using a strong oxidant and acidic medium at high temperatures has been the method of choice, which has served as a very useful tool. [4][5][6][7][8][9] Highly reactive chemicals such as alkali metals and Brønsted super acids have also been employed, often leading to charged CNT-derivatives which are quite unstable under ambient conditions. [10][11][12][13] Given the significant damage caused during these harsh processes, the pristine CNTs tend to ultimately lose their primary properties and often become air sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…[148] In our group, SAMs of SWNTs covalently attached to a (3-aminopropyl)trimethoxysilanemodified ITO surface (SAM-ITO) were prepared from a soluble SWNT, which was safely obtained via a two-step process assisted by microwave irradiation (Scheme 2). [149] It has been reported that SWNTs can be quickly functionalized under the assistance of UV or microwave irradiation, [150,151] plasma or ozone treatment. [152,153] A two-step method was developed to prepare soluble functionalized SWNTs assisted by a microwave oven in our group.…”
Section: Electrochemical Properties C N T S H a V E A H I G H E L E Cmentioning
confidence: 99%
“…[152,153] A two-step method was developed to prepare soluble functionalized SWNTs assisted by a microwave oven in our group. Compared with the preparation under higher pressure, [151] the two-step approach allowed for a safer and easier operation. The FT-IR data of the soluble functionalized SWNTs showed a strong stretching mode of the -COOH groups from the SWNT backbone, and a weaker peak attributed to the asymmetric SO 2 stretching mode of the acid sulfonate (-SO 2 OH) group, which implied that most of the functionalized carbon atoms on the SWNT backbone were carboxylated, with the remainder being sulfonated.…”
Section: Electrochemical Properties C N T S H a V E A H I G H E L E Cmentioning
confidence: 99%